(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Larasati F, Sudiarso, Barunawati N, Aini N. 2022. Monoterpenes accumulation inducing by nutrient status under rhizobacteria and organic manure supply in Cymbopogon nardus. Biodiversitas 23: 4055-4063. The quality type of Cymbopogon nardus in Indonesia is called as Java Citronella Oil. One of the oil components determining the quality of C. nardus is citronellal content as well-known monoterpenes. The citronellal component in C. nardus is obtained through the redistillation process in leaves. This study aims to obtain citronellal content, organic matter, and carbon which are affected by dosage of fertilizer on C. nardus. In the overall, the citronellal component of plants without PGPR (P0) treatment at all levels of organic manure supply is 10% higher than those treated rhizobacteria (P20). The final content of carbon and organic matter in respectively (2,25%) and (3,08%) leaves of plant (P0) at K10, K20, K25, K30 is 20% higher than those treated with P20. This might be caused by the carbon that is distributed to the vegetative part during the fast-growth phase, by contrast, the component of citronellal was reduced. The growth rate of C. nardus depends on the accumulation of dry weight at 5 and 6 MAP, which increases significantly with organic manure treatment of K30 and supply of rhizobacteria (P20), which had nutrient status 1,362% nitrogen, 0,194% phosphorus, 0,882 % potassium in leaf following by citronellal and citronellol.